2006
DOI: 10.1097/01.brs.0000228845.27561.e0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Flexion Relaxation Phenomenon of the Trunk Muscles in Sitting

Abstract: The findings show that the SLM and the IO are facilitated in neutral lordotic sitting postures and exhibit FRP at mid range flexion while moving from upright sitting to slump sitting. These findings show that FRP in sitting differs from that in standing. Variable motor patterns (activation or FRP) of the TES were observed. These findings suggest that sustaining mid to end-range flexed sitting spinal postures result in relaxation of the spinal stabilizing muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
2
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 34 publications
3
71
2
3
Order By: Relevance
“…Previous literature showed that healthy subjects tend to slump into lumbar flexion during prolonged sitting and also demonstrate repositioning errors in sitting and standing postures [41,45,68,69]. Maffey-Ward et al [68] found a between-day error of 2.6°during sitting while Swinkels and Dolan [41] showed between-day errors of 5.27 ± 3.47°d uring lumbar spine sagittal movement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature showed that healthy subjects tend to slump into lumbar flexion during prolonged sitting and also demonstrate repositioning errors in sitting and standing postures [41,45,68,69]. Maffey-Ward et al [68] found a between-day error of 2.6°during sitting while Swinkels and Dolan [41] showed between-day errors of 5.27 ± 3.47°d uring lumbar spine sagittal movement.…”
Section: Discussionmentioning
confidence: 99%
“…Within the sagittal plane, habitual poor postures include forward head and flexed-relaxed postures 4,6) . Both of these positions are easily adopted by computer users due to their low muscular effort, and they result in increased load on passive paraspinal structures 6,7) . Increased forward head, specifically, which combines lower cervical flexion and upper cervical extension with rounded shoulders, might result in weakness of the cervical extensors as well as increased compressive forces in the articulations of the cervical spine 8,9) .…”
mentioning
confidence: 99%
“…Previous research has presented data on the positive relationship between activation of the upper trapezius muscle and flexion of the cervical spine muscles during computer operation 8,10,11) . It has been documented that the disadvantages of flexedrelaxed sitting are that it leads to increased disc pressure, tension in passive structures and flexion relaxation within the pain-free population 7,12) . Therefore, the definition of an ideal sitting posture to avoid poor posture has been discussed in biomechanical and ergonomic arenas.…”
mentioning
confidence: 99%
“…This may ultimately contribute to disc degeneration [29] and may consequently cause LBP. Furthermore, the flexion-relaxation phenomenon is present during slumped sitting [44], so there is very low active muscular support for the lumbar spine. Because of this very low activation, the load is transmitted by passive structures such as the ligaments and IVD.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been much interest in the stability of the lumbar spine and its relation to LBP [23]. On the other hand, a review on posture reported that there are still controversies and little evidence to support the claims of benefits of ideal posture or the suggestion that poor posture will lead to LBP [44].…”
Section: Introductionmentioning
confidence: 99%